(untitled) (AYUSHDHARA, 2015)
Sheetpitta is a Tridoshaja disorder having predominance of Pitta and Vayu and Rasa and Rakta are main Dushyas it can be clinically correlated with urticaria. Urticaria is a dermal vascular reaction of the skin characterized by the appearance of itchy wheals. A 50 year old female patient presented with following complaint - on and off reddish rashes on whole over the body associated with severe itching since four months. She was clinically diagnosed as Sheetpitta or urticaria. The patient was treated with Panchkarma chikitsa and some Ayurvedic Sanshamana drugs. Initially the patient had been administered Snehana with Panchtiktaghrita, Further, Virechana was done with Hritaki (Terminalia chebula), Katuki (Picrorhiza kurroa) and Nishotha (Operculina terpethum) kwath (decoction) followed by Sanshaman therapy. The follow up was done for two months during which she had no episodes of rashes or itching. The results of the treatment were encouraging and there were no side effects during the therapy.